Pivotal role of cerebral interleukin-23 during immunologic injury in delayed cerebral ischemia in mice. (2nd April 2015) - Zheng, Y.; Zhong, D.; Chen, H.; Ma, S.; Sun, Y.; Wang, M.; Liu, Q.; Li, G.
Highlights: IL-23p19 knockdown improves neurological scores and reduces infarct volume. IL-23p19 knockdown reduced the expression of IL-17. IL-23p19 knockdown increased IFN-γ expression. IL-23p19 knockdown had no impact on cytokine IL-4 expression. IL-23p19 knockdown increased Foxp3 expression. Abstract: Background: Interleukin-23 (IL-23) is required for T helper 17 (Th17) cell responses and IL-17 production in ischemic stroke. We previously showed that the IL-23/IL-17 axis aggravates immune injury after cerebral infarction in mice. However, IL-23 might activate other cytokines and transcription factor forkhead box P3 (Foxp3) production in cerebral ischemia. We aimed to determine whether IL-23p19 knockdown prevents cerebral ischemic injury by reducing ischemic-induced inflammation. Methods: Ischemic stroke models were established by permanent middle cerebral arterial occlusion (pMCAO) in male C57BL/6 mice. In vivo gene knockdown was achieved by intravenous delivery of lentiviral vectors (LVs) encoding IL-23p19 short hairpin RNA (LV-IL-23p19 shRNA). Enzyme-linked immunoassay (ELISA) and quantitative real-time polymerase chain reaction (qRT-PCR) confirmed inhibitory efficiency. Behavioral deficits were evaluated by adhesive-removal somatic-sensory test. Brain infarct volume was measured at day 5 after pMCAO by 2, 3, 5-triphenyltetrazolium chloride (TTC) staining. Expression of IL-17, IL-4, interferon (IFN)-γ and Foxp3 in ischemic brain tissues were detected by qRT-PCR and Western blotting, respectively. Additionally, immunohistochemical staining located cytokines in ischemic brain tissues. Results: RNA interference knockdown of IL-23p19 resulted in improved neurological function and reduced infarct volume. IL-23p19 knockdown suppressed IL-17 gene and protein expression. Moreover, IL-23p19 deficiency enhanced IFN-γ and Foxp3 expressions in delayed cerebral ischemic mice, and did not impact IL-4 expression. Immunohistochemical staining showed that IL-17, IL-4, IFN-γ and Foxp3-positive cells were located around ischemic lesions of the ipsilateral hemisphere. Conclusions: IL-23p19 knockdown prevents delayed cerebral ischemic injury by dampening the ischemia-induced inflammation, and is a promising approach for clinically managing ischemic stroke.